2020
DOI: 10.3390/min10090744
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Natural and Recycled Concrete Aggregate Mixtures for Use in Pavement Structures

Abstract: This study investigates the feasibility of using recycled concrete aggregate (RCA) as a partial substitution of natural aggregate in pavement engineering. Despite RCA’s good properties, such as polishing value and freeze-thaw resistance, its use is limited by low resistance to fragmentation and high-water absorption. This paper parent the experimental results of mineralogical-petrographic and physical-mechanical properties of RCA, natural stone (dolerite) and their combination (RCA content—15%, 30%, 45%, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The materials used in these tests, as precursors, were metakaolin and powdered basalt. Ðokić et al [48] used the micro-Deval test to assess the abrasion resistance of the concrete aggregate (RCA) as a partial replacement of natural aggregate in road engineering in different flexible and rigid pavement layers and for various traffic loads. RCA was reached by crushing 30-year-old concrete slabs covered with a protective layer of asphalt.…”
Section: Rock Abrasiveness Test Methods Applicationmentioning
confidence: 99%
“…The materials used in these tests, as precursors, were metakaolin and powdered basalt. Ðokić et al [48] used the micro-Deval test to assess the abrasion resistance of the concrete aggregate (RCA) as a partial replacement of natural aggregate in road engineering in different flexible and rigid pavement layers and for various traffic loads. RCA was reached by crushing 30-year-old concrete slabs covered with a protective layer of asphalt.…”
Section: Rock Abrasiveness Test Methods Applicationmentioning
confidence: 99%
“…The review indicated a growing interest in aggregates obtained from recycling processes. A significant number of publications suggest the possibility of replacing mineral aggregates with recycled aggregates and offer evaluations of the physical and strength-related parameters of such materials [ 1 , 23 , 24 , 25 , 26 , 27 , 28 ]. The results demonstrate that such materials may become an alternative construction material.…”
Section: Wear and Fragmentation Resistance Of Mineral Aggregates—a Review Of Micro-deval And Los Angeles Testsmentioning
confidence: 99%
“…Mineral aggregates are among the most important raw materials mined worldwide and also among the materials most frequently used in civil engineering [ 1 , 2 , 3 , 4 , 5 ]. Adomako et al [ 6 ] observe that crushed stones account for nearly 50% of aggregate production in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral aggregates are the basic raw material used in housing and road construction [ 1 , 2 , 3 , 4 , 5 , 6 ]. In addition to mineral aggregate, other materials can be used in construction as substitute components for the production of building materials [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%